The Effectiveness of Health Counseling using Scrapbook Media on Knowledge About Stunting Among Prospective Brides in Kampung Jawa Lama, Banda Sakti District, Lhokseumawe City - Murniati Murniati; Cut Linar; Mawarni Yunita; Rahmad Mouliansyah; Wulandari Wulandari (International Journal Of Health Science, 2025)
The occurrence of short stature in toddlers, commonly referred to as stunting, is one of the main nutritional problems faced by toddlers in Indonesia today. The results of the Indonesian Nutrition Status Survey (SSGI) in 2022 for each province across Indonesia show that Aceh ranks fourth highest in stunting cases with a percentage of 31.2%. The first position is held by the province of West Sulawesi (35.0%), the second by Papua (34.6%), and the third by West Nusa Tenggara (32.7%). The lowest position is held by the province of Bali (8.0%), followed by the second lowest, DKI Jakarta (14.8%). This type of research is quantitative using the Quasi-Experimental design method with a Two-Group Pretest-Posttest Design. The sampling technique used was total population, consisting of 41 people in the intervention group and 41 people in the control group. The research results show that the average knowledge score about stunting in the intervention group is 28.30 and in the control group is 21.15854. Thus, descriptively, it can be concluded that there is a difference in the average knowledge score about stunting between the intervention group and the control group. The Sig. value of Levene’s Test For Equality of Variances is 0.573 > 0.05, so based on the value in the "Equal variances assumed" table, the Sig. (2-tailed) value is 0.000 < 0.05, meaning the use of scrapbook media in health promotion regarding knowledge about stunting among prospective brides in Kampung Jawa Lama Village, Banda Sakti District, Lhokseumawe City in 2024 is declared effective. The use of scrapbook media in health counseling to increase knowledge among prospective brides in preventing stunting in Kampung Jawa Lama Village, Banda Sakti District, Lhokseumawe City is declared effective.